Fine-grain AlN / AZ91D magnesium-based composite material and extrusion and rolling method thereof
Through solid solution, extrusion, homogenization and annealing, the problems of poor plastic deformation ability of magnesium alloy at room temperature and complex hot rolling process are solved, and fine crystalline AlN/AZ91D magnesium-based composite material is obtained, achieving high performance The production of magnesium alloy cold-rolled sheets reduces production costs and improves efficiency.
Patent Information
- Application Number
- CN202411294119.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-14
AI Technical Summary
Magnesium alloy has poor plastic deformation ability at room temperature, which leads to prone to edge cracks during cold rolling. The existing hot rolling process is complex, high energy consumption, low production cost and efficiency, making it difficult to obtain fine-grained rolled sheets.
The process flow of solid solution treatment, extrusion treatment, homogenization treatment, multi-pass cold rolling, interpass annealing treatment and annealing treatment are adopted to promote recrystallization and continuous precipitation of γ-Mg17Al12 phases through in-situ AlN particles, and refine it. Crystals improve the mechanical properties and formability of magnesium alloys.
It realizes a high-performance magnesium alloy cold-rolled sheet with uniform structure, fine grains and good formability, which reduces production costs, improves production efficiency, avoids edge cracking problems, and significantly improves the mechanical properties of magnesium alloy.
Smart Images

Figure CN119307841A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of plastic deformation of AlN / AZ91D magnesium-based composite materials. Background Art
[0002] The density of magnesium alloy is small (only 1.8g / cm 3 ), as a lightweight metal structural material, its density is equivalent to 2 / 3 of aluminum and about 1 / 4 of steel; at the same time, magnesium alloy has a higher specific strength (ratio of strength to mass), and its specific stiffness (ratio of stiffness to mass) is close to that of aluminum alloy and steel, and much higher than that of engineering plastics. At the same time, magnesium alloy has good recyclability and is environmentally friendly; good thermal conductivity and damping and shock absorption performance; good machining performance, stable part size; good electromagnetic shielding, radiation resistance, biocompatibility and other excellent properties, and is known as the "21st century green engineering metal structural material". The above advantages make magnesium alloy widely used in portable equipment and the automotive industry to achieve the purpose of lightweighting, and also play an important role in aerospace, electronic communications, medical and other fields.
[0003] However, the structure of cast magnesium alloy is not uniform, and shrinkage and slag inclusions often occur in castings, which have a great impact on the performance of magnesium alloy. At the same time, the strength of cast magnesium alloy is low, which limits the application of magnesium alloy as a metal structural material. Deformation processing of magnesium alloy not only makes the structure of magnesium alloy more uniform, but also greatly improves the strength of magnesium alloy to meet the performance requirements of industrial load-bearing structural parts. Extrusion and rolling, as traditional deformation processing methods, have the advantages of high production efficiency, large workpiece size, and low cost, and are widely used in industry. Through extrusion and rolling, the grains can be effectively refined, the microstructure can be regulated, and the mechanical properties of magnesium alloy can be improved.
[0004] Magnesium has a hexagonal close-packed structure (HCP). At room temperature, magnesium alloys have only two independent slip systems, which cannot achieve the conditions for stable and uniform deformation, resulting in poor plastic deformation ability of magnesium alloys at room temperature. This makes it easy for magnesium alloys to crack during cold rolling, and it is difficult to obtain high-performance rolled plates with good formability. In order to improve the formability of magnesium alloys, hot rolling technology is generally used. However, the use of hot rolling technology in production will cause many disadvantages, such as increased equipment complexity, high energy consumption, and inconvenient operation. This will not only increase production costs and reduce production efficiency, but also the performance improvement is not significant.
[0005] The grain size and grain morphology of magnesium alloys have an important influence on their mechanical properties and stamping properties. When the grain size is reduced, the plasticity and strength of magnesium alloys at room temperature will be improved, while the yield strength of magnesium alloys at high temperatures will be reduced, so that the hot stamping performance of rolled plates will be improved. Based on the above reasons, for deformed magnesium alloys, it is generally hoped to obtain fine-grained rolled plates. A large number of theories and production practices have proved that reducing the grain size has a more significant effect on improving the performance of magnesium alloys than aluminum alloys. For example, the effect of reducing the grain size on improving certain properties of magnesium alloys is 4 times that of aluminum alloys. Therefore, it is of great significance to obtain a magnesium alloy structure with fine grains. However, the method of refining grains by severe plastic deformation (SPD), such as equal-diameter angular extrusion (ECAP) and high-pressure torsion (HPT), has low production efficiency in the former and small workpiece size in the latter, making it difficult to apply on a large scale in industry.
[0006] Therefore, being able to provide an extrusion or / and rolling process with low production cost and to obtain a magnesium alloy cold-rolled material with uniform structure, fine grain size and good formability is bound to be of great significance to the magnesium alloy industry. Summary of the invention
[0007] The purpose of the present invention is to avoid the shortcomings of the prior art and provide a fine-grained AlN / AZ91D magnesium-based composite material and its extrusion and rolling method with simple process, easy operation, high production efficiency, improved mechanical properties of magnesium alloy, and ensure that the magnesium alloy has good formability.
[0008] To achieve the above object, the technical solution adopted by the present invention is: an extrusion and rolling method of a fine-grained AlN / AZ91D magnesium-based composite material, comprising the following steps:
[0009] Step 1: Solution treatment of AlN / AZ91D magnesium-based composite ingot:
[0010] The AlN / AZ91D magnesium-based composite material ingot is subjected to a solution treatment at a solution temperature of 400 to 420°C and a solution time of 20 to 25 hours, and then the solution-treated ingot is water-cooled to room temperature;
[0011] Step 2: Extrusion treatment:
[0012] The cooled ingot is subjected to extrusion deformation at an extrusion temperature of 350 to 410° C., an extrusion rate of 2 to 6 cm / min, and an extrusion ratio of 50:1 to 80:1 to obtain an extruded material;
[0013] This step is used to promote the nucleation of recrystallization of in-situ AlN particles and promote the γ~Mg 17 Al 12 The continuous precipitation of phases realizes the grain refinement of AlN / AZ91D magnesium-based composites.
[0014] Step 3: Homogenization:
[0015] Cutting a rectangular plate from the extruded material, and subjecting the rectangular plate to a homogenization heat treatment at a temperature of 400 to 410° C. for 10 to 20 minutes;
[0016] This step is used to improve the coordinated deformation ability between grains of the AlN / AZ91D magnesium-based composite material.
[0017] Step 4: Multiple cold rolling and annealing between passes:
[0018] The homogenized rectangular plate is subjected to multiple cold rolling in a roller, the upper and lower roller speeds during cold rolling are 6.3-12.6 r / min, the rolling temperature is below 350°C, and the first rolling reduction is 15-20%, and the subsequent rolling reduction is 10-15% for each pass; the annealing temperature between passes is 340-360°C, the annealing time is 2-3 minutes, and the total reduction is 75-85%, and finally a cold rolled plate is obtained;
[0019] This step is used to dynamically recrystallize the rectangular plate and promote the γ~Mg 17 Al 12 Phase separation.
[0020] Step 5: Annealing treatment:
[0021] The cold-rolled sheet is annealed at an annealing temperature of 270 to 300° C. for 1 to 1.5 hours. After the annealing is completed, the cold-rolled sheet is water-cooled to room temperature to obtain a fine-grained AlN / AZ91D magnesium-based composite material;
[0022] This step is used to eliminate stress concentration and work hardening, and to precipitate γ~Mg 17 Al 12 The phase produces a pinning effect, thereby inhibiting grain growth.
[0023] Furthermore, the original blank of the AlN / AZ91D magnesium-based composite material ingot in step 1 is a rod blank of Φ100±20×130±30, and the solution treatment is carried out in a heat treatment furnace.
[0024] Furthermore, in the step 2, the surface oxide scale of the cooled ingot is removed, and the ingot is subjected to a heat treatment at a temperature of 360 to 400° C. for 1 to 1.5 hours before being subjected to extrusion deformation.
[0025] Furthermore, the extruded material obtained in step 2 has a grain size of 20 to 30 μm, a tensile strength of 310 to 340 MPa, and an elongation of 15 to 25%.
[0026] Furthermore, in step three, the surface of the rectangular plate is polished with #800, #1200, and #1500 SiC sandpaper in sequence until it is smooth and then subjected to homogenization heat treatment.
[0027] Furthermore, the rectangular plate after the homogenization heat treatment in step three has a room temperature plasticity of 28-35%, a tensile strength of 310-340 MPa and a yield strength of 200-220 MPa.
[0028] Furthermore, the rollers in step 4 are not heated.
[0029] Furthermore, the grain size of the cold-rolled sheet obtained in step 4 is 10 to 14 μm.
[0030] Furthermore, the annealing treatment described in step five is performed in a muffle furnace.
[0031] The present invention also provides a fine-grained AlN / AZ91D magnesium-based composite material obtained by the above extrusion and rolling method, wherein the fine-grained AlN / AZ91D magnesium-based composite material has a grain size of 10-12 μm, a yield strength of 210-250 MPa, an elongation of 18-24%, and no surface cracks.
[0032] The beneficial effects of the present invention are as follows: the present invention uses the cast AlN / AZ91D magnesium-based composite material as a raw material, and finally obtains a high-performance magnesium alloy cold-rolled sheet with uniform structure, fine grains and good formability by formulating a reasonable solid solution process, an extrusion process, a homogenization process, a rolling process and an annealing process;
[0033] In particular, the cold rolling process of the present invention has a low rolling temperature and a short annealing time between passes, which can effectively save energy and improve production efficiency; wherein, the rollers do not need to be heated, and the rolling process is synchronous rolling, which greatly simplifies the rolling equipment and further reduces production costs. The magnesium alloy cold-rolled sheet obtained by this method not only avoids the problem of edge cracking during the rolling process, but also greatly improves the mechanical properties of the magnesium alloy;
[0034] At the same time, the present invention is also a process for industrially producing large-scale fine-grained magnesium alloy plates, which is of great significance for refining grains, reducing production costs, improving yield rates, and expanding the application range of magnesium alloy plates. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 : A process flow chart of the extrusion and rolling method of the AlN / AZ91D magnesium-based composite material of the present invention;
[0036] Figure 2 : AlN / AZ91D magnesium-based composite extruded rod of the present invention;
[0037] Figure 3 : Stress-strain curve of the rectangular plate after homogenization treatment of the present invention;
[0038] Figure 4 : AlN / AZ91D magnesium-based composite cold-rolled sheet of the present invention;
[0039] Figure 5 : Microstructure diagram of the cold-rolled sheet after annealing treatment of the present invention. DETAILED DESCRIPTION
[0040] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0041] The AlN / AZ91D magnesium-based composite ingot used in the present invention is prepared by a Chinese patent with authorization announcement number CN105463232B. The ingot has a high room temperature strength and plasticity combination. In order to further improve its mechanical properties and meet the performance requirements of industrial load-bearing structural parts, it needs to be deformed.
[0042] In order to achieve the above-mentioned purpose, the present invention performs a solution treatment on the ingot before extrusion, performs a hot extrusion forming after preheating, and then cuts a rectangular plate from the extruded material. In order to obtain a relatively uniform structure, eliminate the residual stress in the material after extrusion processing, and improve its plasticity for subsequent rolling, the extruded material needs to be homogenized. In the subsequent rolling process, the reduction amount of each pass, the annealing temperature and the annealing time need to be strictly controlled, so that a cold-rolled plate with fine grains and good formability can be finally obtained.
[0043] After rolling, in order to eliminate work hardening, remove stress concentration generated during rolling, and promote recrystallization and refinement of grains, the cold-rolled sheet needs to be annealed. Through the optimal ratio of the above process parameters, the process flow is shown in Figure 1 As shown, the final magnesium alloy extruded material and cold-rolled sheet with good formability, excellent performance and fine grains are obtained.
[0044] The present invention provides the following specific implementation modes:
[0045] Example 1: Figures 1 to 4 As shown, a method for extruding and rolling a fine-grained AlN / AZ91D magnesium-based composite material comprises the following steps:
[0046] Step 1: Solution treatment of AlN / AZ91D magnesium-based composite ingot:
[0047] The AlN / AZ91D magnesium-based composite material ingot is cast, and the original billet of the ingot is a rod billet of Ф100±20×130±30. The solution treatment is carried out under the conditions of a solution temperature of 400-420°C and a solution time of 20-25h, and then the ingot after solution is water-cooled to room temperature; the solution treatment is carried out in a heat treatment furnace.
[0048] Step 2: Extrusion treatment:
[0049] The surface oxide scale of the cooled ingot is removed, and after heat treatment at a temperature of 360-400° C. for 1-1.5 hours, extrusion deformation is performed under the conditions of an extrusion temperature of 350-410° C., an extrusion rate of 2-6 cm / min, and an extrusion ratio of 50:1-80:1 to obtain an extruded material, which is specifically as follows Figure 2 The extruded bars shown;
[0050] The grain size of the extruded rod after the treatment is 20-30 μm, the tensile strength is 310-340 MPa, and the elongation is 15-25%.
[0051] Step 3: Homogenization:
[0052] Cutting a rectangular plate from the extruded rod, and grinding the surface of the rectangular plate with #800, #1200, and #1500 SiC sandpapers in sequence until smooth, and then performing a homogenization heat treatment at a temperature of 400 to 410° C. for 10 to 20 minutes;
[0053] The rectangular plate after homogenization heat treatment has a plasticity of 28-35%, a tensile strength of 310-340 MPa and a yield strength of 200-220 MPa. The tensile stress-strain curve is as follows: Figure 3 As shown, from Figure 3 It can be seen that the rectangular plate after heat treatment has a high room temperature strength and plasticity combination.
[0054] Step 4: Multiple cold rolling and annealing between passes:
[0055] The homogenized rectangular plate is subjected to multiple cold rolling in a roller, the upper and lower roller speeds during cold rolling are 6.3-12.6 r / min, the rolling temperature is below 350°C, and the first rolling reduction is 15-20%, and the subsequent rolling reduction is 10-15% for each pass, and the rollers are not heated; the annealing temperature between passes is 340-360°C, the annealing time is 2-3 minutes, and the total reduction is 75-85%, and finally a cold rolled plate is obtained;
[0056] After the treatment in step 4, the grain size of the cold-rolled sheet is 10-14 μm. Figure 4 As shown, from Figure 4It can be seen that the surface quality of the cold-rolled plate is good and no cracks appear.
[0057] Step 5: Annealing:
[0058] In a muffle furnace, the cold-rolled sheet is annealed at an annealing temperature of 270 to 300° C. for 1 to 1.5 hours. After the annealing is completed, the cold-rolled sheet is water-cooled to room temperature to obtain a fine-grained AlN / AZ91D magnesium-based composite material;
[0059] The present invention has formulated a reasonable solid solution process and extrusion process. The extruded rod has good formability and no cracks on the surface. During the hot extrusion process, the in-situ AlN particles promote the nucleation of recrystallization, resulting in a significant grain refinement of the extruded AlN / AZ91D magnesium-based composite material. The grain size is reduced from 84μm to 26μm, a reduction of 69%. In addition, compared with the extruded AZ91 alloy, a high-density dislocation is generated during the extrusion deformation process to adapt to the strain incompatibility between the AlN particles and α-Mg, promoting the γ-Mg 17 Al 12 The continuous precipitation of phase. Therefore, due to the grain boundary strengthening and precipitation strengthening, the strength of the magnesium alloy is significantly improved. At the same time, during the stretching process, the non-basal slip system of the AlN / AZ91D magnesium-based composite extruded rod is activated, so that the AlN / AZ91D magnesium-based composite extruded rod has higher plasticity at room temperature.
[0060] Compared with the cast AlN / AZ91D magnesium-based composite material, the tensile strength of the extruded AlN / AZ91D magnesium-based composite material increased from 210.8MPa to 328.2MPa, an increase of 55.7%; the elongation increased from 14.3% to 16.3%, an increase of 14.0%. The extruded AlN / AZ91D magnesium-based composite material has a high combination of strength and plasticity. After homogenization treatment, the internal stress distribution of the AlN / AZ91D magnesium-based composite material is more uniform, the grains rotate, the texture strength is reduced, the base is deflected, and the coordinated deformation ability between the grains is increased, so the room temperature plasticity is significantly improved.
[0061] After homogenization treatment, the room temperature plasticity of the rectangular plate of AlN / AZ91D magnesium-based composite material increased from 16.3% to 33%, an increase of 102.5%; while the tensile strength and yield strength only decreased by 0.2% and 4.5%, respectively, which laid a good foundation for subsequent cold rolling deformation.
[0062] In the cold rolling process, the optimal ratio of rolling temperature parameters, pass reduction parameters and inter-pass annealing time parameters is achieved, and finally a cold-rolled sheet with no edge cracks on the surface and good formability is obtained. The rolling temperature can be controlled at 350°C or below, and the inter-pass annealing time is within 3 minutes, which greatly improves the rolling efficiency. In the cold rolling process, as the number of rolling passes increases, the grain size continues to decrease. This is because a large number of dislocations and twins are introduced during the rolling process, dynamic recrystallization occurs, and at the same time, the γ-Mg 17 Al 12 Phase precipitation, in the subsequent annealing process, the precipitated phase produces a pinning effect, inhibiting grain growth. The microstructure of the cold-rolled sheet is a large number of fine dynamic recrystallized grains, and there are no twins in the grains. After rolling and deformation, the grain size of the material is reduced from 26μm to 13μm, a decrease of 50%. In order to eliminate stress concentration and work hardening, the cold-rolled sheet is annealed. Static recrystallization occurs during the annealing process, and the grain size is reduced from 13μm to 12μm. At the same time, this also shows that the cold-rolled sheet has good grain size stability and the grains are not easy to grow at high temperatures.
[0063] The present invention uses high-strength and plastic AlN / AZ91D magnesium-based composite material ingots as raw materials, and through continuous optimization of solid solution, extrusion, rolling, annealing and other processes, finally obtains high-performance extruded bars and cold-rolled plates with uniform structure, fine grain size and good formability. The process has short annealing time, simple operation and low cost, and can be applied to the industrial production of large-scale fine-grained magnesium alloy plates, which is of great significance for expanding the application range of magnesium alloy plates.
[0064] Example 2: Figure 5 As shown, the present invention also provides a fine-grained AlN / AZ91D magnesium-based composite material obtained by the above-mentioned extrusion and rolling method, wherein the fine-grained AlN / AZ91D magnesium-based composite material has a grain size of 10 to 12 μm, a yield strength of 210 to 250 MPa, an elongation of 18 to 24%, and no surface cracks.
[0065] Depend on Figure 5 It can be seen that the microstructure of the cold-rolled plate after annealing is a large number of fine dynamically recrystallized grains, no twins appear in the grains, and the grain size is relatively uniform.
[0066] The present invention provides an extrusion and rolling method for a fine-grained AlN / AZ91D magnesium-based composite material, performs cold rolling deformation on the basis of the extruded AlN / AZ91D magnesium-based composite material, determines the solid solution process before extrusion deformation, formulates a reasonable extrusion process and a subsequent homogenization annealing process, optimizes the rolling process and the final annealing process, and the magnesium alloy cold-rolled sheet obtained by the method provided by the present invention not only avoids the edge cracking problem in the rolling process, but also greatly improves the mechanical properties of the magnesium alloy, and the rolled sheet has uniform structure, fine grains and good formability.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for extruding and rolling a fine-grained AlN / AZ91D magnesium-based composite material, characterized in that: The following steps are involved: Step 1: Solution treatment of AlN / AZ91D magnesium-based composite ingot: The AlN / AZ91D magnesium-based composite material ingot is subjected to a solution treatment at a solution temperature of 400 to 420°C and a solution time of 20 to 25 hours, and then the solution-treated ingot is water-cooled to room temperature; Step 2: Extrusion treatment: The cooled ingot is subjected to extrusion deformation at an extrusion temperature of 350 to 410° C., an extrusion rate of 2 to 6 cm / min, and an extrusion ratio of 50:1 to 80:1 to obtain an extruded material; Step 3: Homogenization: Cutting a rectangular plate from the extruded material, and subjecting the rectangular plate to a homogenization heat treatment at a temperature of 400 to 410° C. for 10 to 20 minutes; Step 4: Multiple cold rolling and annealing between passes: The homogenized rectangular plate is subjected to multiple cold rolling in a roller, the upper and lower roller speeds during cold rolling are 6.3-12.6 r / min, the rolling temperature is below 350°C, and the first rolling reduction is 15-20%, and the subsequent rolling reduction is 10-15% for each pass; the annealing temperature between passes is 340-360°C, the annealing time is 2-3 minutes, and the total reduction is 75-85%, and finally a cold rolled plate is obtained; Step 5: Annealing treatment: The cold-rolled sheet is annealed at a temperature of 270 to 300° C. for a time of 1 to 1.5 h. After the annealing is completed, the cold-rolled sheet is water-cooled to room temperature to obtain a fine-grained AlN / AZ91D magnesium-based composite material.
2. The extrusion and rolling method of the fine-grained AlN / AZ91D magnesium-based composite material according to claim 1, characterized in that: The original blank of the AlN / AZ91D magnesium-based composite material ingot in step 1 is a bar blank of Φ100±20×130±30, and the solution treatment is carried out in a heat treatment furnace.
3. The extrusion and rolling method of the fine-grained AlN / AZ91D magnesium-based composite material according to claim 1, characterized in that: In the step 2, the surface oxide scale of the cooled ingot is removed, and the ingot is subjected to heat treatment at a temperature of 360 to 400° C. for 1 to 1.5 hours before being subjected to extrusion deformation.
4. The extrusion and rolling method of the fine-grained AlN / AZ91D magnesium-based composite material according to claim 1, characterized in that: The extruded material obtained in step 2 has a grain size of 20 to 30 μm, a tensile strength of 310 to 340 MPa, and an elongation of 15 to 25%.
5. The extrusion and rolling method of the fine-grained AlN / AZ91D magnesium-based composite material according to claim 1, characterized in that: In step three, the surface of the rectangular plate is polished with #800, #1200, and #1500 SiC sandpapers in sequence until it is smooth and then subjected to homogenization heat treatment.
6. The extrusion and rolling method of the fine-grained AlN / AZ91D magnesium-based composite material according to claim 1, characterized in that: The rectangular plate after the homogenization heat treatment in step three has a room temperature plasticity of 28-35%, a tensile strength of 310-340 MPa and a yield strength of 200-220 MPa.
7. The extrusion and rolling method of the fine-grained AlN / AZ91D magnesium-based composite material according to claim 1, characterized in that: The rollers described in step 4 are not heated.
8. The extrusion and rolling method of the fine-grained AlN / AZ91D magnesium-based composite material according to claim 1, characterized in that: The grain size of the cold-rolled sheet obtained in step 4 is 10 to 14 μm.
9. The extrusion and rolling method of the fine-grained AlN / AZ91D magnesium-based composite material according to any one of claims 1 to 8, characterized in that: The annealing treatment described in step 5 is carried out in a muffle furnace.
10. A fine-grained AlN / AZ91D magnesium-based composite material obtained by the extrusion and rolling method according to claims 1 to 9, characterized in that: The fine-grained AlN / AZ91D magnesium-based composite material has a grain size of 10-12 μm, a yield strength of 210-250 MPa, an elongation of 18-24%, and no surface cracks.
Citation Information
Patent Citations
A kind of preparation method of high-strength and high-plasticity Aln / az91d magnesium-based composite material
CN105463232B